The Influence of Instagram-based Digital Literacy and Learning Interest on Learning Outcomes in the Subject of Al-Qur'an Hadith - Annisa Dahlila Angelina; Candra Wijaya; Haidir Haidir (EDUTEC : Journal of Education And Technology, 2023)
This study aims to determine: (1) The effect of Instagram-based digital literacy on student learning outcomes of Al-Qur'an Hadith at Madrasah Tsanawiyah Maura El-Mumtaz Binjai, (2) The effect of student interest in learning Al-Qur'an Hadith at Madrasah Tsanawiyah Maura El-Mumtaz Binjai Madrasah Tsanawiyah Maura El-Mumtaz Binjai. (3) The effect of digital literacy and interest in learning on student learning outcomes in Al-Qur'an Hadith subject at Madrasah Tsanawiyah Maura El-Mumtaz Binjai. This research was conducted at Madrasah Tsanawiyah Maura El-Mumtaz Binjai which is located at Jl. Sei Batanghari No. 6 Tanah Seribu Village, South Binjai District, Binjai City. The findings of this study indicate that: Instagram-based digital literacy has an influence on Learning Outcomes in Al-Qur'an Hadith Subject of students at Madrasah Tsanawiyah Maura El-Mumtaz Binjai by 15.4%, student learning interest has an influence on Learning Outcomes on Eyes Al-Qur'an Hadith lessons for students at Madrasah Tsanawiyah Maura El-Mumtaz Binjai by 30.1%, digital literacy and student interest in learning together have an influence on Learning Outcomes in Al-Qur'an Hadith Subjects for students at Madrasah Tsanawiyah Maura El-Mumtaz Binjai is 47% while the remaining 53% comes from outside the variables of this study.